Mechatronics - Leniowska, Lucyna (Ed.) (University of Rzeszów, 2011)
Mechatronics may be popularised in various manners and it is necessary to begin with the aspect of history. It may be started from its contemporary applications and benefits resulting from that or the review of crucial construction, electronic and algorithm solutions. The second manner is sometimes more interesting, more encouraging to familiarise yourself with. I rely on this cognitive curiosity while handing you this publication. This publication includes 13 articles, divided into four sections. The first section includes 4 works regarding medical applications. Medicine is undergoing a period of increased interest from technical sciences. Applications in the scope of biomechanics, biotechnology, biomimetics and bionics, medical robotics or telemedicine change the methods and measures applied not only in rescuing human life, but diagnosing, treating and the rehabilitation of patients as well. The synergy of the aforementioned disciplines remaining in the circle of interest of mechatronics begins to bring more and more spectacular results. The first chapter includes the review of the most important domestic and global solutions regarding medical robots, as well as presents an original structure of a manipulator, assigned for minimally invasive operations. In the second chapter, the methodology of mechatronic designing has been presented, as a result of which there is an original prototype of a hand-based grab, designed for a humanoid robot. The third chapter includes the concept of planning the trajectory for an “intelligent” wheelchair. The author’s project assumes the construction of a vehicle combined with a complex IT system which would provide great autonomy of disabled persons on the basis of processed city plans with GPS marks. The fourth chapter is dedicated to several examples depicting the principles of applying Computer Aided Engineering systems in medicine. As a result, doctors obtain a new device for medical diagnosis and preoperative planning. The second section includes 5 works on the problems of modelling and controlling in application for various mechatronic systems. The first chapter presents studies aimed at creating a modern, adaptive mechatronic system for active noise reduction, which has much potential in places of limited communication, including emergency communication. In the second chapter, the idea of creating a mechatronic system based on an adaptive algorithm has been presented. Its role relies on the active reduction of vibrations of constructive elements (panels) which may have a significant, negative impact on functioning machines and devices, deteriorating the working conditions of an operator. The third chapter is devoted to a system assigned for reducing audio and video noises. The application of Least Mean Squareshas been discussed on the basis of experiments in the nVidia CUDA environment. The fourth chapter regards broadly understood issues of modelling and connected computer simulations which are an indispensable element of the process of mechatronic designing. Also presented in this chapter is a program component developed by the authors – a “physical engine” which is part of a simulator - original software for complex simulations of dynamic systems, working in real time and characterised by a high reliability of calculations. The final chapter presents the concept of use in unmanned aircrafts, in order to increase safety coefficients of passenger flights. The solution which includes fuzzy control, assumes that one or more unmanned flying objects may become an element of another flying object, enriching its capabilities, e.g. overtaking the existing parts in emergency situations. The third section is devoted to technological problems defined as an “intelligent house”. It includes two chapters, in which the original solutions are presented of the control system equipment layer of an “intelligent house” based on access to technologies (mechanical, electromechanical, electronic solutions) commonly known standard of data transmission as well as own solutions in the scope of algorithms and software. These solutions are characterised by a low cost of manufacturing, simplicity and openness to future modifications, according to the changing needs of users. The final, fourth section, “Technological problems”, presents other less typical applications of mechatronic systems connected with e.g. problems of automating the determination of certain substances or providing reliability and durability of a product.
Mechatronika (wersja polska)
Keywords: mechatronics, surgical robots, design of gripping, wheelchair, CAE systems for planning surgical operations, fast LMS algorithm, adaptive control in mechatronical systems, intelligent house control system; surgical robots; design of gripping; wheelchair; CAE systems for planning surgical operations; fast LMS algorithm; adaptive control in mechatronical systems; intelligent house control system